Reducing Nitrogen Waste: Factors Influencing Neem‐Coated Urea Adoption in Bhutan - Toritseju Begho; Tashi Dorji; Sonam Dendup (Modern Agriculture)
ABSTRACT In Bhutan, farmers face constraints due to limited arable land, prompting a need to increase agricultural production per unit of inputs, but in the most sustainable way given the nation’s most stringent environmental conservation laws. This study investigates the factors influencing the adoption of an enhanced‐efficiency fertiliser, that is, neem‐coated urea (NCU). Analysing data from 235 farmers using a double hurdle regression model, the paper identified several positive drivers of NCU adoption, including multiple plots, larger farm size, organic fertiliser use, recent agricultural training, and seeking advice on fertiliser decisions. Conversely, factors such as irrigation, crop demonstration attendance, machinery subsidies, rigid fertiliser usage adherence, perceived difficulty in handling fertilisers, and attitudes towards soil and crop management hinder adoption. Older farmers exhibit higher adoption rates, potentially due to accumulated knowledge, while male farmers surpass their female counterparts in adoption rates, reflecting existing gender disparities in NCU adoption. These findings offer insights for policymakers, extension services, and agricultural stakeholders to tailor interventions for promoting NCU adoption, thereby mitigating nitrogen waste and pollution in crop production.